"From the tenacious networks of the World Wide Web - to the exalted heights of knowledge" (a view from an elementary school) - O. I. Shyman (Academy of Cognitive and Natural Sciences, 2013)
The key technologies of the modern information society are telecommunications and the Internet. To prepare the younger generation for life in this society, we need an education system that will be based on a cloud infrastructure and the use of its electronic educational resources. Every year more and more Ukrainian children use the Internet in everyday life. Any manufactured electronics today and planned for release tomorrow (desktops, laptops and netbooks, tablets and smartphones) certainly have a key function required for work in the World Wide Web - a browser. The use of cloud technologies, aimed at supporting open education, creates the conditions for organizing remote and mobile access not only to teaching materials, but also to learning tools placed on the Internet.